Chemically interconnected light-weight 3D-carbon nanotube solid network. (August 2017) - Ozden, Sehmus; Tsafack, Thierry; Owuor, Peter S.; Li, Yilun; Jalilov, Almaz S.; Vajtai, Robert; Tiwary, Chandra S.; Lou, Jun; Tour, James M.; Mohite, Aditya D.; Ajayan, Pulickel M.
Abstract: Owing to the weak physical interactions such as van der Waals and π-π interactions, which hold nanotubes together in carbon nanotube (CNT) bulk structures, the tubes can easily slide on each other. Creating covalent interconnection between individual carbon nanotube (CNT) structures could remarkably improve the properties of their three-dimensional (3D) bulk structures. The creation of such nanoengineered 3D solid structures with improved properties and low-density remains one of the fundamental challenges in real-world applications. Here, we report the scalable synthesis of low-density 3D macroscopic structure made of covalently interconnected nanotubes using free-radical polymerization method after functionalized CNTs with allylamine monomers. The resulted interconnected highly porous solid structure exhibits higher mechanical properties, larger surface area and greater porosity than non-crosslinked nanotube structures. To gain further insights into the deformation mechanisms of nanotubes, fully atomistic reactive molecular dynamics simulations are used. Here we demonstrate one such utility in CO2 uptake, whose interconnected solid structure performed better than non-interconnected structures. Graphical abstract: